18F-FDG PET/MR-imaging in a Göttingen Minipig model of atherosclerosis: Correlations with histology and quantitative gene expression. (June 2019) - Ludvigsen, Trine P.; Pedersen, Sune F.; Vegge, Andreas; Ripa, Rasmus S.; Johannesen, Helle H.; Hansen, Adam E.; Löfgren, Johan; Schumacher-Petersen, Camilla; Kirk, Rikke K.; Pedersen, Henrik D.; Christoffersen, Berit Ø.; Ørbæk, Mathilde; et al.
Abstract: Background and aims: The advantage of combining molecular and morphological imaging, e.g. positron emission tomography and magnetic resonance imaging (PET/MRI), is reflected in the increased use of these modalities as surrogate end-points in clinical trials. This study aimed at evaluating plaque inflammation using 18 F-fluorodeoxyglucose ( 18 F-FDG)-PET/MRI, and gene expression in a minipig model of atherosclerosis. Methods: Göttingen Minipigs were fed for 60 weeks with fat/fructose/cholesterol-rich diet (FFC), chow (Control) or FFC-diet changed to chow midway (diet normalization group; DNO). In all groups, 18 F-FDG-PET/MRI of the abdominal aorta was assessed midway and at study-end. The aorta was analyzed using histology and gene expression. Results: At study-end, FFC had significantly higher FDG-uptake compared to Control (target-to-background maximal uptake, TBRMax (95% confidence interval) CITBRMax : 0.092; 7.32) and DNO showed significantly decreased uptake compared to FFC (CITBRMax : -5.94;-0.07). No difference was observed between DNO and Control (CITBRMax : −2.71; 4.11). FFC displayed increased atherosclerosis and gene expression of inflammatory markers, including vascular cell adhesion molecule 1 ( VCAM-1 ), cluster of differentiation 68 ( CD68 ), matrix metalloproteinase 9 ( MMP9 ), cathepsin K ( CTSK ) and secreted phosphoprotein 1 ( SPP1 ) compared to Control and DNO (all, p < 0.05). FDG-uptake correlated with gene expression of inflammatory markers, including CD68, ρs = 0.58; MMP9, ρs = 0.46; SPP1, ρs = 0.44 and CTSK, ρs = 0.49; ( p ≤ 0.01 for all). Conclusions: In a model of atherosclerosis, 18 F-FDG-PET/MRI technology allows for detection of inflammation in atherosclerotic plaques, consistent with increased inflammatory gene expression. Our findings corroborate clinical data and are important in pre-clinical drug development targeting plaque inflammation. Graphical abstract: Image 1 Highlights: Diet-induced minipig model displays advanced human-like atherosclerosis. Correlation between ex vivo and in vivo assessment of plaque inflammation. Translational large animal model for targeting inflammation in atherosclerosis.